FUNCTIONAL HEALTH LITERACY ON DIABETES MELLITUS AND ANTI-DIABETIC DRUGS (Journal of Forensic Medicine & Toxicology, 2019)
Neoteric advances in the diversified anti-diabetic drugs have resulted in the startling increase in the number of poisoning cases.This demandthe alertness concerning diabetes heath care to signify the gravity of education as a key public health position marker in computing for the expanded prevalence of diabetes mellitus. Theextensive survey focuses on diabetes mellitus health care employing ten diverse realms for investigating the relationship between self-proclaimed literacy level and assessed literacy level. Electronic Data Capture (EDC) System and Paper-based data collection method were used in collection of primary data. Data is bestowed as age-wise and gender wise percentage distribution. Study revealed that 58% respondents have responded with probable diabetic type whereas 42% respondents, being a diabetic does not even know about their diabetes type. 79% of diabetic population do not even concerned about their medication they are taking on regular basis. Study also acknowledged the current prescribing pattern of anti diabetic drugs involving metformin with 44% prescription rate followed by glimepiride (sulphonyl urea) and DDP 4 inhibitors (Dipeptidylpeptidase- 4- inhibitors) with 24% and 8% prescription rate respectively.
Keywords: Diabetes mellitus; Functional health literacy; anti-diabetic drugs; Blood-glucose level; Questionnaire